2019
DOI: 10.1002/nur.21970
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial work environment and cross‐cultural competence among native and foreign‐born registered nurses

Abstract: Cross‐cultural competence is an essential component of the nursing profession, but little is known about the specific psychosocial work characteristics that potentially promote or hinder such competence. In the present study, psychosocial work characteristics were based on Karasek's Job Demand—Control Model. The researchers examined whether Karasek's psychosocial work characteristics, such as high‐strain jobs, high‐strain isolated jobs, active jobs, and active collective jobs, are associated with cross‐cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The main objective of the present study was to test the efficacy of the JDCS model for predicting WLB among nursing professionals. Nursing presents its own particularities and is critical for maintaining the welfare state in Europe; however, nursing care takes place in one of the most stressful work environments that exists [96]. As noted by Karatepe and Uludag (2007), the health care sector is unique due to its high level of stress and its intense physical, psychological, and emotional demands [99].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main objective of the present study was to test the efficacy of the JDCS model for predicting WLB among nursing professionals. Nursing presents its own particularities and is critical for maintaining the welfare state in Europe; however, nursing care takes place in one of the most stressful work environments that exists [96]. As noted by Karatepe and Uludag (2007), the health care sector is unique due to its high level of stress and its intense physical, psychological, and emotional demands [99].…”
Section: Discussionmentioning
confidence: 99%
“…This method is one of the most frequently applied statistical approaches for developing social prediction models with binary results [91,92]. Logistic regression has been used with the Karasek model for example [93][94][95] and specifically in the field of nursing (for example, [96][97][98]). This method allows the determination of the probability that a certain event-good balance between personal and professional life-will occur compared with the probability that the opposite event will occur.…”
Section: Measures and Methodology: The Binary Logistic Regression Modelmentioning
confidence: 99%
“…The assumption of active learning hypothesis is to work with high job demands and high job control and at the same time to stimulate learning of new skills and to allow the search for new coping strategies. The improvement of employee performance and personal development is facilitated by active work (Wesołowska et al, 2019).…”
Section: Social Competencies and Psychosocial Properties Of Nurses' W...mentioning
confidence: 99%
“…Many studies have indicated the importance of social competencies in medical professions (including nursing) and patient care, evidence of which is found in many areas, such as communication (Amoah et al, 2019; Hashim, 2017; Sanson‐Fisher et al, 2019), interpersonal contacts (Matczak & Martowska, 2013; Smarżewska, 2019), teamwork (Blažun et al, 2015; Lown & Manning, 2010), professional work aspects (Losa‐Iglesias et al, 2017; Niitsuma et al, 2012), area of emotion (Lee & Seomun, 2016; Matczak, 2007), stress and burnout (Losa‐Iglesias et al, 2017; Pereira‐Lima & Loureiro, 2015; Uchiyama et al, 2011), quality of care (Amoah et al, 2019; Haley et al, 2017; Lown & Manning, 2010), and patient‐centred care (Haley et al, 2017; Hashim, 2017; Lown & Manning, 2010; Wesołowska et al, 2019) (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation